Plankton Food Web Responses to Experimental Nutrient Additions in a Subtropical Lake - Karl E. Havens; Therese L. East (The Scientific World Journal)
During two controlled enclosure experiments using water from a subtropical lake, the plankton food web displayed a highly variable response to combined addition of nitrogen and phosphorus. In July, the nutrients stimulated growth of Cylindrospermopsis raciborskii, and the biomass of macrozooplankton and microbial food web components did not increase. In October, the same addition of nutrients stimulated growth of small edible Lyngbya spp., and there were coincident increases in biomass of macrozooplankton and components of the microbial web. Past generalizations that cyanobacteria blooms inhibit growth of other food web components may not always hold true.